Comparison Effects of Vaginal Misoprostol with Vaginal Evening Primrose on Ripening Cervix in Nulliparous Women - Mirzadeh, Narges; Sheikhan, Zohre; Simbar, Masoumeh; Mehrolhasani, Yasamin; Saffar, Azam; Yeganeh, Zohreh (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Childbirth requires several changes in the function of the uterus and cervix. Today, various methods are used to prepare the cervix. Ripening of the cervix is one of the most factors in a successful delivery. This study aims to compare the effects of vaginal misoprostol tablet with vaginal evening primrose capsule on cervical ripening in nulliparous women with term pregnancy. Methods: This study was a randomized clinical trial of a sokor conducted on 100 nulliparous women referred to Pasteur Hospital and Prenatal Clinic of University of Medical Sciences of Bam, 40 weeks to 40 weeks±6 days gestational age with Bishop Score less than 4. The women were selected by convenient sampling based on random numbers divided into two groups, evening primrose (1000 mg vaginal evening primrose capsules) and misoprostol (25 micrograms of vaginal misoprostol tablets). The data was collected by demographic and midwifery questionnaire, follow-up form, Bishop’s checklist, fetal movement registration form, and daily record. Data were analyzed by SPSS20 software, independent t-test, Mann-Whitney, Chi-square, and Linear by Linear. In all of the tests, P < 0.05 was considered. Results: Bishop’s score at admission in the evening primrose group was 1.84 ± 0.88 versus 0.78 ± 0.66 in the misoprostol group (P < 0.001). The two groups had significant differences in terms of dilatation and cervical consistency during admission. The dilatation in the evening primrose group significantly increased, and cervical consistency was considerably softer in the misoprostol group (P < 0.05). Conclusions: It seems that evening primrose is more effective on cervical ripening and dilatation.